Game-based Learning at the Primary Level: Enhancing Education through Play - S, Angel Rathnabai (THE PRIMARY TEACHER, 2019)
Game-based learning (GBL), an innovative educational approach, has gained increasing recognition and adoption in primary education globally. Utilising games as an instructional tool in primary schools has been demonstrated to be an effective and engaging method for improving learning outcomes. By incorporating educational content into game scenarios, educators can make the learning process enjoyable, interactive, and meaningful for young students. This article examines the advantages and implementations of game-based learning at the primary education level, highlighting its potential to make learning fun, engaging, and effective.